New Zealand species of the genus Tripyla Bastian, 1865 (Nematoda:Triplonchida: Tripylidae). I : A new species, a new record and key to long-tailed species - Zhao, Zeng Qi (Zootaxa, 2009)
This paper describes two species of the genus of Tripyla from New Zealand and also provides a key to species based on the morphology of females in eight long-tailed (c < 5) species in the genus of Tripyla. Tripyla bioblitz sp. nov. is characterized by its more anterior vulva position (V = 43.7–45.4%), relatively short body length (1150–1410 μm) and long tail (c = 4.0–4.4) in the group. Tripyla filicaudata de Man, 1880 is recorded for the first time from New Zealand and from the Southern Hemisphere. In addition, the phylogenetic relationships among species were analyzed using data from the near full length small subunit (SSU) and D2/D3 expansion segments of the large subunit ribosomal (LSU) rRNA genes, and these analyses revealed that T. bioblitz sp. nov. is close to but distinct from T. filicaudata de Man, 1880.